Analysis of Cryptocurrency Financial Reporting Based on PSAK - Ayu Kurnia Sari; Vina Arnita; Hendra Saputra; Oktarini Khamilah Siregar; Rica Cahya Amalya (Harmony Management: International Journal of Management Science and Business, 2025)
Cryptocurrency in Indonesia has begun to develop and is starting to be widely used by businessmen in Indonesia. This is a phenomenon given the need for accounting treatment for cryptocurrency transactions. This research seeks to explore and test cryptocurrency and blockchain technology with the approach and review of PSAK in Indonesia and focuses on accounting treatment for cryptocurrencies in Indonesia. The purpose of this study is to conduct an accounting study for cryptocurrencies based on PSAK that applies in Indonesia. The study used a review literature model to figure out accounting for cryptocurrencies.